Qualidade física de solos irrigados do Rio Grande do Sul e do Brasil central - Michelon, Cleudson José (2005)
The irrigated áreas are caracterized by an intensification of the land use, and as consequence, an intense use of the soil. This usually results in a higher pressure of the soil structure degradation, causing many times soil compaction. The main cause is the intensive traffic of machines and equipments, that usually occurs an soil with higher soil water content. The soil compaction modifyes some soil physical characteristics, decreasing soil aeration, decrease water infitration and increasing the mechanical resistance of the soil, affecting root growing and development. The objetive of this study was to carry out soil physical characterization of irrigated areas of some Brazilian regions and collect informations necessary to guide soil management decisions. Soil sampling were taken in irrigated areas cultivated under a central pivot irrigation system, in the Rio Grande de Sul State (RS) and central region of Brazil. The soil profile was divided in three soil layers: superficial, intermediate and inferior. Samples were collected in the median portion of each soil layer and the following determinations: were conducted: soil texture, bulk density (Bd), particles density, porosity and the water content of the soil water potential of -0.001, -0.006, -0.033, -0.01, -0.5 and -1.5 Mpa. Soil types were grouped in seven ranges of clay content: 0-20; 20-30; 30-40; 40-50; 50-60; 60-70 and ligher than 70% of clay. For each clay content a critical values of bulk density (Bd) and of the soil macroporosity (macro) were established values (above and below the Bd and macro critical level) to classify as soil compacted. The indication of soil compaction was grouped in four levels: NC - no compacted; CD - indication of soil compaction due to Bd; CM - indication of soil compaction due to macroporosity and CDM - indication of soil compaction due to both: Bd and macroporosity. The majority of soil samples colleted in the RS was classified in the range of 40-50% of clay content in the superficial layer and in the range higher than 70% in the intermediate and inferior soil layers. In the Goias State (GO), the majority of soil samples were classified in the range of clay content higher than 70% in the three soil profile layers. In Minas Gerais State (MG) the majority of soil sample collected was classified in the range of 20-30% of clay content in the superficial and 30-40% of clay content in the intermediate and inferior layers. In the Bahia State (BA), the majority of soil sample collected was classified in the range of 0-20% of clay content, in the three layers of the profile. Considering the entire area sampled in the RS 66.5% presented indication of soil compaction in the superficial layer, 25% in the intermediate layer and 9.5% in the inferior layer. The superficial layer of the soil profile presented the highest frequency of soil samples with indication of soil compaction for the levels of CM and CDM for the range of 40-50% of clay content, and the range of 50-60% of clay content in the compaction level of CD. However, in the central region of Brazil; 13.3% of the areas in GO, 24.1% of the areas in MG, and 29.2% of the areas in BA had preseted indication of soil compaction in the superficial layer. In BA the collected soil samples in the superficial layer in the range 0-20% of clay content presented the highest frequency of indication of soil compaction for the leves CD, CM and CDM. In the state of GO and MG the highest indication of soil compaction in the superficial layer was observed for the CM level and occurred in the ranges of 20-30 and 30-40% of clay content.